Struktura wydatków osób zwiedzających zabytki militarne (na przykładzie Wilczego Szańca w Gierłoży) - Gabryjończyk, Piotr (Zeszyty Naukowe SGGW - Ekonomika i Organizacja Gospodarki Żywnościowej, 2012)
The paper is dedicated to the economic aspect of tourism in military attraction such as Wolf’s Lair (Hitler’s headquarter) in Gierłoż. It presents its brief history, with focus on construction process, as well as some details about operational history and modern day of the fortifications. The second part of the paper concentrates on problematic of domestic sightseer’s expenses in Wolf’s Lair and shows their dimension, as well as the eternal structure, with focus on buyers of gastronomic services and role of the income in deciding about this kind of outgoings. Finally, some observations about local pricing and suggestions of its welcome changing were given.